Spatial variation of seed rain in deciduous tropical forest (Research, Society and Development, 2020)
Seed rain is an ecological process and its functional attributes are essential for maintaining the dynamics of natural regeneration. The objective of this research was to evaluate the spatial variation of the seed rain in a toposequence of a Seasonal Deciduous Forest defined by three elevations: (Base 512 m; Slope: 534 m and Top: 559 m). 15 collectors of 1 m² were installed at each elevation level. Data were collected monthly from September / 2017 to February / 2019. The seeds were classified according to the dispersion syndrome, habit and size. Non-Metric Multidimensional Scaling (NMDS) was used to verify the variation in species composition and distribution. We identified 20,217 propagules, belonging to 65 species and 30 families, in addition to 4 morphospecies, which represents 449 seeds / m². The families with the highest species richness were Fabaceae, Sapindaceae and Euphorbiaceae. Of the 65 species sampled, 71% were arboreal. Zoochoric species predominated (78%) and very small seeds corresponded to 53% of the sample. We demonstrate that, on a small spatial scale, the relief represents an important source of heterogeneity in the vegetation component, since the topographic gradient influenced the composition and distribution of the functional attributes of the seed rain.